Kompetensi ASN Pariwisata dan Pengembangan Pelatihan Berbasis Kompetensi - Lia Afriza; Er Ummi Kalsum; Ananta Budhi Danurdara (Manajemen dan Pariwisata, 2026)
This study aims to analyze the competency level of public servants (ASN) in the tourism sector, identify the root causes of competency gaps, and formulate an appropriate Competency-Based Training (CBT) model aligned with regional tourism development needs. The problem arises from non-competency-based job rotation, the absence of substantive tourism training, low digital literacy, and the lack of technical institutional standards within tourism offices. This research employs a qualitative method through field observation, in-depth interviews with non-managerial and non-functional tourism staff, and literature review of relevant regulations, including the Ministry of Administrative Reform (PermenPANRB) regulations from 2020–2023, the ASN Competency Dictionary (2022), and national tourism development policies. The findings reveal that ASN competencies remain weak across the five core pillars of tourism: (1) destination management, due to limited understanding of planning and standardization; (2) tourism marketing, reflected in the lack of digital promotion and branding skills; (3) institutional governance, characterized by minimal coordination and the absence of operational SOPs; (4) tourism human resource development, where ASN are not yet capable of providing substantive guidance to tourism actors; and (5) the tourism industry, marked by insufficient knowledge of industry structure and value chains. These competency gaps are primarily caused by non-merit job rotation practices, the absence of technical tourism training for implementing staff, inadequate institutional support, and the rapid evolution of the tourism sector that surpasses the rate of competency development among ASN. Based on these findings, this study recommends the adoption of a Competency-Based Training (CBT) model that includes modules on destination management, digital tourism marketing, institutional governance, tourism human resource development, tourism industry understanding, and digital literacy using data and geographic applications. The proposed CBT model is designed based on actual job requirements and competency gap analysis to ensure measurable, sustainable improvement of ASN capabilities. Implementing CBT is essential to developing professional, adaptive public servants capable of meeting the increasingly complex demands of the tourism sector.